Study of Antioxidant Properties of Compounds from Kratom Leaves (Mitragyna speciosa) Using the Density Functional Theory (DFT) Method - Arief, Ihsanul; Kurnianto, Erwan; Khairi, Syahrul (Chemistry Department, The University of Brawijaya, 2025)
At least 17 compounds in kratom leaves (Mitragyna speciosa) are responsible for several pharmacological activities, one of which is antioxidant. This study examines antioxidant activity based on thermodynamic aspects in the form of HOMO-LUMO energy values, and kinetics in the form of predictions of radical quenching mechanisms. All compounds were optimized for geometry, and thermodynamic parameters were determined in the form of energy gap values (ΔE), ionization potential (IP), electron affinity (EA), hardness (η), electronic chemical potential (µ), softness (S), and electrophilicity index (Ω). The compounds that showed the most superior potential were then predicted for their radical quenching mechanisms by determining the values of bond dissociation energy (BDE), ionization potential (IP), proton dissociation enthalpy (PDE), proton affinity (PA), and electron transfer enthalpy (ETE). The results of the analysis of thermodynamic properties showed that three compounds had the most potential values, namely speciociliatine, 7-hydroxy mitragynine, and mitraphylline. The study of the radical scavenging mechanism of the three compounds shows that the compounds had antioxidant activity through the hydrogen atom transfer (HAT) mechanism.